Title: IDENTIFYING THE AXILLARY NERVE DURING SHOULDER SURGERY: AN ANATOMIC STUDY USING ADVANCED IMAGING - Hachadorian, Michael E. (Orthop J Sports Med, 2021)
BACKGROUND: The axillary nerve (AXN) is one of the more commonly injured nerves during shoulder surgery. Prior anatomic studies of the AXN in adults were performed using cadaveric specimens with small sample sizes. Our research observes a larger cohort of magnetic resonance imaging (MRI) studies in order to gain a more representative sample of the course of the axillary nerve and aid surgeons intraoperatively. METHODS: High-resolution 3T MRI studies performed at our institution from January 2010 to June 2019 were reviewed. Four blinded reviewers with musculoskeletal radiology or orthopaedic surgery training measured the distance of the AXN to the surgical neck of the humerus (SNH), the lateral tip of the acromion (LTA), and the inferior glenoid rim (IGR). Intra-class Correlation Coefficient (ICC) was calculated to assess reliability between reviewers. The nerve location was assessed relative to rotator cuff tear status. RESULTS: A total of 257 shoulder MRIs were included. ICC was excellent at 0.80 for SNH, 0.90 for LTA and 0.94 for IGR. All intra-observer reliabilities were above 0.80. Mean distance from AXN to SNH was 1.7 cm (0.7-3.1 cm, IQR 1.38-2.00) and AXN to IGR was 1.6 cm (0.6-2.6 cm, IQR 1.33-1.88). The mean AXN to LTA distance was 7.1 cm, with a range of 5.2 to 9.0 cm across patient heights; there was a large effect size related to LTA to AXN distance and patient height with a correlation of r=0.603, (p<0.001). Rotator cuff pathology appears to affect nerve location by increasing the distance between AXN and SNH (p = 0.027). DISCUSSION/CONCLUSION: The AXN is vulnerable to injury during both open and arthroscopic shoulder procedures. This injury can be either a result of direct trauma to the nerve or secondary to traction placed on the nerve with reconstructive procedures that distalize the humerus. Our study demonstrates that the axillary nerve can be found as little as 5.6 mm from IGR and 6.9 mm from the SNH. Additionally, we illustrate the relationship between patient height and LTA to AXN distance and complete rotator cuff tears and SNH to AXN distance. Our study is the first to demonstrate the nerve’s proximity to important surgical landmarks of the shoulder using a large sample size of high-resolution images in living human shoulders. TABLES/FIGURES: